2012
DOI: 10.1136/archdischild-2011-300526
|View full text |Cite
|
Sign up to set email alerts
|

Lyme meningitis, the major cause of childhood meningitis in an endemic area: a population based study

Abstract: LM was diagnosed in two-thirds of children with infectious meningitis in this LB endemic area. Distinct clinical characteristics distinguished the majority of children with LM from children with non-Lyme aseptic meningitis and bacterial meningitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 38 publications
3
21
0
3
Order By: Relevance
“…In adults, ACA has an estimated prevalence of 1-2% among all LB patients with skin manifestations and preferentially affects elderly people in Europe (11). We found that SEM affects boys and girls equally as the most typical skin manifestation of early LB with a median incubation period and disease duration of one week, which is comparable with prior literature (11)(12)(13)(14)(15)(16) days) (20,21,36). The majority of SEM in our children (79%) and in previous European studies (46-58%) (20,21) occurred at the site of a recalled tick bite.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In adults, ACA has an estimated prevalence of 1-2% among all LB patients with skin manifestations and preferentially affects elderly people in Europe (11). We found that SEM affects boys and girls equally as the most typical skin manifestation of early LB with a median incubation period and disease duration of one week, which is comparable with prior literature (11)(12)(13)(14)(15)(16) days) (20,21,36). The majority of SEM in our children (79%) and in previous European studies (46-58%) (20,21) occurred at the site of a recalled tick bite.…”
Section: Discussionsupporting
confidence: 90%
“…For example, ACA typically affects elderly adults, whereas BL is primarily diagnosed in children (11,14). Peripheral facial nerve palsy and aseptic meningitis are the most common neurologic manifestation of LB in children (3,9,10,16,17), whereas adults are commonly affected by radiculoneuritis (5). Data suggest that Lyme arthritis is more frequent in children than in adults (3,18), but runs a more favorable course as 10% of adults but very few children develop chronic Lyme arthritis (3,19).…”
mentioning
confidence: 99%
“…The inclusion criteria for the various diagnostic groups were defined prior to the start of the study, and the children were subsequently allocated to the groups based on laboratory findings upon admission, as shown in Table 1 and as described in more detail elsewhere (23). Children with probable LNB were considered likely to have LNB because LNB is the predominant cause of aseptic meningitis in children in this region (24), and it has been shown previously that this group has a clinical presentation similar to that of children with confirmed LNB in this area (9). In this study of PCR for B. burgdorferi sensu lato, all diagnostic groups listed in Table 1 were included, except for the nonmeningitis group, because the inclusion criteria for this group were wide, and we expected that this group would include a large number of children with an unclear likelihood of having LB and a low pretest probability of having positive PCR results.…”
Section: Methodsmentioning
confidence: 99%
“…Incidence of NB among children in some European countries, where this disease is endemic, is higher than among adults (3) and it is the main cause of meningitis (4). Sex-dependent differences in the incidence of NB among children were reported.…”
Section: Introductionmentioning
confidence: 97%